8A.03: CONTINUOUS MONITORING OF HEMODYNAMICS IN THE SHORT ARM HUMAN CENTRIFUGE. (June 2015) - Londono, F.; Uytterhaegen, B.; Kassel, R.; Vanraemdonck, R.; Beck, A.; Comet, B.; Runge, A.; Segers, P.
Abstract : Objective: The aim was to test the technical feasibility of a set up combining tonometry and ultrasound, designated as Continuous Physiological and Medical Monitoring (CPMM), for cardiovascular assessment on humans and to evaluate the ability to assess physiological changes induced by artificial gravity in the short arm human centrifuge (SAHC, Verhaert, Belgium) for detecting and preventing potential disorders induced by weightlessness. Design and method: The project was developed under an European Space Agency (ESA) contract (4000101988/10/NL/EM) and with its support, by the company Verhaert in consortium with the Institute for Space Medicine and Physiology (MEDES) and Ghent University. Measurements were performed at MEDES facilities in 4 young (presumably) healthy volunteers (3 males). For two volunteers, the protocol was divided in three periods: acceleration, steady rotation velocity and deceleration, obtaining carotid pulsed wave (PW)-Mode ultrasound sequences. For another volunteer (female), carotid PW-Mode ultrasound images and brachial and radial tonometry signals were acquired at baseline and during steady rotation. For the fourth volunteer, carotid and femoral PW-Mode ultrasound images and brachial, radial and carotid tonometry signals were acquired at baseline and during an initial (velocity1) and a following faster (velocity2) rotation velocity (see figure on the following page). Results: Carotid PW-Mode ultrasound imaging was obtained in all 4 volunteers during different steps of the protocol. Femoral ultrasound imaging presented more difficulties related mainly to the placement of the probe after baseline, even if in one case results were feasible. Tonometry was, generally, a bigger challenge due to the intrinsic sensitivity of the method. Overall, radial artery tonometry provided the best results, while brachial artery results were acceptable only in one occasion. Carotid tonometry was measured only for one subject with suitable results for processing. Conclusions: Tonometry measurements were feasible under a spin velocity limit, while PW-Mode ultrasound images were more robust and stable. Although general conclusions must be supported by a larger sample, suitable signals and locations were identified and a user friendly and mobile set-up was tested successfully and it is available for further research to identified and assess mechanisms and reflexes acting in physiological adaptation to various gravity conditions. Figure. No caption available.